PROBLEM FACED BY THE RURAL AREA STUDENTS IN LEARNING ENGLISH SPEAKING - Zarah Amelia H. Basri; Sriati Usman; Abdul Kamaruddin; Wahyudin Wahyudin (e-Journal of ELTS (English Language Teaching Society), 2022)
This research focuses on students who live in rural areas in learning English speaking. The objective of the research is to find out the problems in speaking skills and to find out the causes of speaking problems in speaking skills encountered by the eighth-grade students of MTs.Muhammadiyah Tolitoli. MTs Muhammadiyah School was located in Baolan district, Tolitoli regency, in Central Sulawesi. The method of this research is qualitative research method while the sample of this research was the eighth-grade students of MTs. Muhammadiyah Tolitoli was chosen by convenience sampling. Observation, interviews, and Questionnaires were the tools of data collection. Based on the data collected from questionnaires, interviews, and observations, it was found that skill factors are the most dominant problem than knowledge factors. It was found that 80% were problems with lack of confidence, 60% were problems with less motivation, and 60 % had problems with feeling shy in learning English speaking. It is followed by the knowledge factor which means a percentage of 72% the aspect of knowledge in learning speaking, 56% pronunciation, and 52% lack of vocabulary. The causes of speaking problems encountered by the eighth-grade students of MTs. Muhammadiyah Tolitoli is inhibition, environment, and mother tongue used.